The rest-frame UV luminosity function at z ≃ 4: a significant contribution of AGNs to the bright end of the galaxy population. Issue 2 (13th March 2020) - Adams, N J; Bowler, R A A; Jarvis, M J; Häußler, B; McLure, R J; Bunker, A; Dunlop, J S; Verma, A
ABSTRACT: We measure the rest-frame ultraviolet (UV) luminosity function (LF) at z ∼ 4 self-consistently over a wide range in absolute magnitude (−27 ≲ M UV ≲ −20). The LF is measured with 46 904 sources selected using a photometric redshift approach over ∼6 deg^2 of the combined Cosmological Evolution Survey and XMM–Newton Large-Scale Structure fields. We simultaneously fit for both active galactic nuclei (AGNs) and galaxy LFs using a combination of Schechter or double power law (DPL) functions alongside a single power law for the faint-end slope of the AGN LF. We find a lack of evolution in the shape of the bright end of the Lyman-break galaxy (LBG) component when compared to other studies at z ≃ 5 and evolutionary recipes for the UV LF. Regardless of whether the LBG LF is fit with a Schechter function or DPL, AGNs are found to dominate at M UV < −23.5. We measure a steep faint-end slope of the AGN LF with α _ AGN = -2.09^+0.35_-0.38 (-1.66^+0.29_-0.58 ) when fit alongside a Schechter function (DPL) for the galaxies. Our results suggest that if AGNs are morphologically selected it results in a bias to lower number densities. Only by considering the full galaxy population over the transition region from AGN to LBG domination can an accurate measurement of the total LFs be attained.